ANALISIS STABILITAS PARIWISATA PEDESAAN SEBAGAI KONDISI YANG SESUAI DENGAN PARIWISATA BERKELANJUTAN - Winda Fuji Anggina (Warta Pariwisata, 2022)
Sustainable development in rural areas can develop from the tourism sector, because it can create jobs and stabilize the level of profit received. A comparison of rural, coastal, and urban destinations was carried out in this study to determine the problems related to seasonal tourism on an annual basis in tourist destinations in Spain. This study answers the question of whether seasonal tourism in a rural setting can be a problem or not. In addition, the purpose of this analysis is to provide an overview of the relationship between rural tourism stability and other theories and models of sustainable tourism. Keywords: Sustainable Tourism, Rural Tourism, Tourism Stability